(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
The article examines the interaction of oral folk art and Russian literature, their mutual influence and ideological and artistic interdependence throughout the 18th and 20th centuries. Particular attention is paid to the works of A.S. Pushkin, V.A. Zhukovsky, M.Yu. Lermontov, I.S. Turgenev, F.M. Dostoevsky, and S.A. Yesenin, where folklore elements play a significant role in shaping the plots, images, and language of works. Folklore has influenced the development of literary genres, expanded the literary canon, and contributed to the preservation of national self-awareness. The features of folklore stylization, secondary folklore, and their connection to mythopoetic traditions are also considered.